2003
DOI: 10.1034/j.1600-0404.2003.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Interictal serum S100B levels in chronic neurocysticercosis and idiopathic epilepsy

Abstract: Serum S100B is normal in patients with focal epilepsy related or not to chronic NCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…These results are also in agreement with data reported by Portela et al (35) that revealed no changes in serum S100B levels in patients with epilepsy and chronic NC. However, in their series only patients (N = 20) harboring inactive forms were considered.…”
Section: Discussionsupporting
confidence: 83%
“…These results are also in agreement with data reported by Portela et al (35) that revealed no changes in serum S100B levels in patients with epilepsy and chronic NC. However, in their series only patients (N = 20) harboring inactive forms were considered.…”
Section: Discussionsupporting
confidence: 83%
“…As previously mentioned, S100B is widely used as a marker for epileptic disorders [ 31 , 32 ], and its secretion is modulated by anti-inflammatory drugs [ 35 , 36 ]. Our studies have suggested that the hippocampal and CSF S100B are altered after SE induction in the Li-pilocarpine model [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The S100B protein is a glial protein that is a widely used marker for brain injury conditions, including epileptic disorders [ 31 , 32 ], and indeed displays an augmented secretion during brain injury condition, working as a neurotrophic cytokine or simply as a damage-associated molecular pattern (DAMP) [ 33 ]. Moreover, S100B secretion is modulated by LPS [ 34 ] and anti-inflammatory drugs [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum neurotropic protein S100B, secreted and synthesized by oligodendrocyte and astroglia, is a sensitive indicator of brain injury [43]. Pathological changes, such as proliferation of gliocytes, damage of blood brain barrier, demyelinating of central nerves, and neuron injury that take place in the brain after epileptic seizure, lead to increased S100B protein [44,45]. In the current study, we showed that levetiracetam treatment lowered S100B protein levels in patients with refractory epilepsy (P \ 0.05).…”
Section: Discussionmentioning
confidence: 45%